Parliamentarism in the Republic of Kazakhstan and Japan: general and special. - Balakayev, L Т (Journal of Oriental Studies, 2016)
This article attempts to analyze the features of formation and development of parliamentarism of the Republic of Kazakhstan and Japan, to determine the general and the particular features. Have been analyzed the main stages of the development of democratic processes in Kazakhstan since 1990 and a special way of political development in Japan which was based on tradition and accelerated modernization in conditions of total democratization of all aspects of social life. Assesses Kazakh and Japanese model of political reform. It reveals general and specific features of parliamentary development of the two countries.